2022
DOI: 10.3920/wmj2021.2766
|View full text |Cite
|
Sign up to set email alerts
|

A review of toxigenic fungi and mycotoxins in feeds and food commodities in West Africa

Abstract: Fungal contamination is a threat to food safety in West Africa with implications for food and feed due to their climate, which is characterised by high temperatures and high relative humidity, which are environmental favourable for fast fungal growth and mycotoxin production. This report gives perspective on studies on toxigenic fungi (Aspergillus, Fusarium and Penicillium) and their toxins, mainly aflatoxins, fumonisins and ochratoxins commonly found in some West African countries, including Benin, Burkina Fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 130 publications
0
4
0
Order By: Relevance
“…Mycotoxins are toxic fungal secondary metabolites that contaminate a wide spectrum of essential foods worldwide, including staple crops consumed by the most vulnerable populations (1). Foodstuffs in West Africa are commonly affected by mycotoxins (2,3) since the climate, where there is high temperature and humidity, is favorable for their production (4,5). Maternal nutrition affects both the pregnancy’s process and the newborn’s well-being (6).…”
Section: Introductionmentioning
confidence: 99%
“…Mycotoxins are toxic fungal secondary metabolites that contaminate a wide spectrum of essential foods worldwide, including staple crops consumed by the most vulnerable populations (1). Foodstuffs in West Africa are commonly affected by mycotoxins (2,3) since the climate, where there is high temperature and humidity, is favorable for their production (4,5). Maternal nutrition affects both the pregnancy’s process and the newborn’s well-being (6).…”
Section: Introductionmentioning
confidence: 99%
“…In Egypt, it was observed that AFB1 and aflatoxin B2 (AFB2) were both present in animal feedstuff ranging from 0.851 to 1.363 µg/kg [ 13 ]. Even, AFB1 concentrations of 1067 µg/kg have been reported in poultry feed in West Africa, highlighting the widespread presence of AFs in feed commodities [ 14 ]. In sub-Saharan Africa, poultry feeds were co-contaminated with more than 21 mycotoxins and/or metabolites [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there has been an alarming increase in mycotoxin contamination, leading to a significant decline in the yield and quality of agricultural produce (Mahato et al 2021 ; Zhong et al 2018 ). Approximately 25% of the food output worldwide is contaminated by mycotoxins (Aasa et al 2022 ), necessitating the continuous demand to ensure the protection of human and animal health by combating mycotoxin exposure on a global scale. Patulin (PAT) is one of the most commonly isolated mycotoxins in apples and apple products (McKinley and Carlton 1980 ).…”
Section: Introductionmentioning
confidence: 99%